Perlindungan Hukum terhadap Perempuan Korban Pelecehan Seksual secara Verbal di Lingkungan Umum (Catcalling) - Aderiatati (Veteran Law Review, 2024)
Verbal sexual harassment or commonly called catcalling is verbal sexual harassment behavior that occurs in public by uttering indecent, sensitive remarks or words at the victim, causing feelings of fear, discomfort and threat. Usually the form of catcalling is in the form of whistling, harsh words containing pornographic elements, innuendo, shouting, and comments aimed at women's physical characteristics.  Generally, catcalling often occurs in public places.  This harassment is often considered normal by society because people think it is just an ordinary joke.  The normative research method used in this research is research based on legal materials by studying written regulations, theories, concepts and secondary data.  This research aims to find out what form of legal protection is provided by the Indonesian State against catcalling harassment, to find out the causes and impacts of catcalling on women.  Women are subjected to harassment on the streets, but there are no specific regulations regarding this case.  Therefore, there needs to be an emphasis on eradicating this harassment to the wider community through regulations related to decency, namely Articles 281 and 289 of the Criminal Code, Law 12/2022 concerning TPKS, and Law 44/2008 concerning Pornography.